Influence of Deposition on the Mechanical Property Correlation in Al-O Thin Films with Complex Microstructures by RF Magnetron Sputtering - R. , Hariharan; R. , Raja (International Journal of Psychosocial Rehabilitation, 2019)
AL-O films were ready on un warmed 4140 steel abstract by RF magnetron sputtering technique. Post-deposition hardening of AL-O films in vacuum was found to enhance film structure and electrical characteristics like dense structure, swish surface stress relief and increase electrical resistance appropriate hardening temperature conjointly reduced loss issue. The coordination between hardening conditions and also the body of the films (crystalline structure and microstructure) was examined by X-ray diffraction (XRD) scanning electron microscopy (SEM) atomic force microscopy(AFM) and FESEM with EDAX. The mechanical behaviour of nanocrystalline CNC metals has attracted widespread interest through the bulk of efforts have centred on economically pure metals.